Basalt fiber manufacturing technology and the possibility of its use in dentistry; IOP Conference Series: Materials Science and Engineering; Vol. 98 : Interdisciplinary Problems of Nanotechnology, Biomedicine and Nanotoxicology (Nanobiotech 2015) - Karavaeva E.; Rogozhnikov A.; Nikitin V.; Cherepennikov Yu. M. Yuriy Mihaylovich; Lysakov A. (2015, 2015)
Title screen